2013
DOI: 10.1002/cmdc.201300354
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design, Synthesis and Structure–Activity Relationships of Thiazolidinones with Enhanced Anti‐Trypanosoma cruzi Activity

Abstract: Pharmacological treatment of Chagas disease is based on benznidazole, which displays poor efficacy when administered during the chronic phase of infection. Therefore, the development of new therapeutic options is needed. This study reports on the structural design and synthesis of a new class of anti-Trypanosoma cruzi thiazolidinones (4 a-p). (2-[2-Phenoxy-1-(4-bromophenyl)ethylidene)hydrazono]-5-ethylthiazolidin-4-one (4 h) and (2-[2-phenoxy-1-(4-phenylphenyl)ethylidene)hydrazono]-5-ethylthiazolidin-4-one (4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Indeed, hydrazine double-bond C2¼N2 is commonly assigned as E configuration [4,23,28]. Concerning the exocyclic double-bond N3¼C3, we suggest that the predominant configuration is in Zconfiguration [7,29]. Besides, a representative 1 H-NMR spectrum of compound 6i is presented in Supplementary Material.…”
Section: Chemistrymentioning
confidence: 84%
“…Indeed, hydrazine double-bond C2¼N2 is commonly assigned as E configuration [4,23,28]. Concerning the exocyclic double-bond N3¼C3, we suggest that the predominant configuration is in Zconfiguration [7,29]. Besides, a representative 1 H-NMR spectrum of compound 6i is presented in Supplementary Material.…”
Section: Chemistrymentioning
confidence: 84%
“…Moreover, some studies have showed that cyclization of thioureas/thiosemicarbazides into thiazole/thiazolidine derivatives is beneficial for Trypanosoma cruzi inhibition when compared to the antiparasitic activity of thiosemicarbazone derivatives [17]. 4-Thiazolidinone derivatives have been studied as potent trypanocidals since the 2000s, giving more active and less toxic lead compounds every year [18][19][20][21][22]. Our previous findings showed good antitrypanosomal activity of thiazolidinone-pyrazoline hybrids [23,24].…”
Section: Introductionmentioning
confidence: 89%
“…Flavanone derivatives were evaluated for anti-T. cruzi activity against the intracellular forms of the parasite. Although the use of epimastigotes present in the midgut vector may be utilized for initial screening [19,20], we have instead opted for the simultaneous use of trypomastigote and intracellular amastigotes forms that are present during both acute and chronic phases of the disease [21,22]. This approach is in accordance with the Drugs for Neglected Diseases Initiative guidelines (DNDi) [23].…”
Section: Evaluation Of In Vitro Anti-t Cruzi Activitymentioning
confidence: 99%